Cinematography. 8 mm film. Image areas. Specification for positions and dimensions of printed 8 mm Type S image area on 35 mm motion-picture film perforated 8 mm Type S, 2R-4.227(1664) or 5R-4.234(1667) Part 1.2.4, (31st October 1978) - British Standards Institution,
No abstract available